Effect of temperature and humidity regimes on grain mold sporulation and seed quality in sorghum (Sorghum bicolor (L.) Moench) - Tonapi, V.A.; Mundada, R.R.; Navi, S.S.; Reddy, R.K.; Thakur, R.P.; Bandyopadhyay, Ranajit; Seetharama, N. (Informa UK Limited, 2007)
Grain mold, induced by a number of non-specific fungi, causes substantial loss to seedgrain yield and quality in sorghum (Sorghum bicolor (L.) Moench). Fungal sporulation and grain mold severity are greatly influenced by temperature and relative humidity (RH) levels. We studied the effects of three incubation temperatures (25, 27 and 288C) and two sets of RH levels (first set: 85, 90, 95, 98, and 100%, second set: 95, 96, 97, 98, 99 and 100%) on sporulation and grain mold severity in three major mold fungi (Curvularia lunata, Fusarium moniliforme, and Bipolaris australiensis) and on four each of resistant, moderately resistant and susceptible sorghum genotypes for sporulation and mold severity of major fungi. Results indicated that both fungal sporulation and grain mold severity increased on most sorghum genotypes with increasing incubation temperature from 25 – 288C and RH levels from 95 –98%. A linear relationship was observed among RH levels, grain mold severity and fungal sporulation. The highest sporulation of all the three fungi occurred at 288C and 98% RH after 5 days of incubation. Among the three fungi, C. lunata grew and sporulated faster than B. australiensis and F. moniliforme, in that order. Among the sorghum genotypes, IS 25017 supported the least sporulation and had the lowest mold severity, followed by IS 8545 and PVK 801. Seed quality parameters, such as seed germination, seedling vigor index, field emergence potential, dehydrogenase and þ-amylase activities declined significantly with increasing temperature and RH levels that supported heavy sporulation and grain colonization.